Termination of the Operational Period of Coal-Fired Power Plants amid Indonesia’s Sustainable Development Plan - Wibawa, Annisa Aninditya (Law Research Review Quarterly, 2025)
Amid Indonesia’s sustainable development plan, Indonesian government Presidential Regulation of the Republic of Indonesia Number 112 of 2022 concerning the Acceleration of Renewable Energy Development for Electricity Supply aims to terminate the operational period of coal-fired power plants. However, the regulation also provides exemptions for the development of new coal-fired power plants under certain conditions. The author analyzes the influence of environmental issues on Presidential Regulation 112/2022 regarding the termination of coal-fired power plants' operational periods, as well as the influence of economic issues on the exemptions for new coal-fired power plants outlined in the regulation. In analyzing the issues, the author uses a socio-legal approach, supported by primary legal materials literature related to sociology of law and sustainable development, as well as news and other credible sources from the internet are also used for this research.